Chracterization on two isolates of potato virus Y and ultrastructural alteration of host cells infected with the two isolates - GUO Xing-qi; LI Xiang-dong; WANG Xiu-fang; ZHU Xiao-ping; WEN Fu-jiang (浙江大学学报. 农业与生命科学版)
The present paper gives detailed description about the differences of two isolates of potato virus Y (PVY) in biological properties, morphology of purified virus particle, serological relationship and the ultrastructural alterations in infected tobacco. The two isolates (i. e., PVY-T and PVY-P) were obtained from tobacco and potato fields in Shandong province, respectively. Based on tests on the host ranges and symptoms on different hosts, the stability in sap in vitro, aphid transmissibility and serological properties, the PVY-T isolate is proved belonging to the PVYO strain group, while the PVY-P isolate was confirmed similarity to PVYN. Meanwhile, the ultrastructural alterations caused by the infection of PVY-T and PVY-P were also investigated. Our results showed that the cytopathological effects of PVY-T differed obviously from that of PVY-P. These characteristic differences might be useful in the virus diagnosis and identification of PVY strains.